Pengaruh Supply Chain Management Di PT. Nippon Indosari Corpindo - Saputra, Raihan; Pasaribu, Aisyah Fitri (Jurnal Manajemen Akuntansi (JUMSI), 2022)
Supply Chain Management is a series of business activities carried out starting from the planning, controlling, implementing the product flow, to the product distribution process to consumers. The purpose of this study was to determine the effect of supply chain management at PT Nippon Indosari Corpindo. The research method used by the researcher is a qualitative method by means of a literature review. The results obtained by researchers are PT Nippon Indosari Corpindo, Tbk. run a complete Supply Chain Management process without cutting the distribution section to save costs.